Ustavnosodna presoja na področju kolektivnih delovnih razmerij - Korpič-Horvat, Etelka (Delavci in delodajalci, 2016)
The author presents and analyses the decisions of the Constitutional Court of the Republic of Slovenia that refer to the right to strike determined by Article 77 of the Constitution. In addition to other Constitutional Court decisions that refer to the right to strike, the author highlights the decision in which the Constitutional Court decided that military personnel are not allowed to strike. In the last part of the article the author underlines open questions that refer to the conditions that must be fulfilled in order for the right to strike to be restricted in accordance with the second paragraph of Article 77 of the Constitution.
Keywords: delodajalci; delovna razmerja; delovni spor; pravice; pravna ureditev; prepoved; sindikati; stavke; zaposleni